The rate of biodegradation of PHA bioplastics in the marine environment: A meta-study. (May 2019) - Dilkes-Hoffman, Leela Sarena; Lant, Paul Andrew; Laycock, Bronwyn; Pratt, Steven
Abstract: There is a reasonably extensive body of literature recording mass loss of polyhydroxyalkanoates (PHAs) (a class of biodegradable plastics) in the natural marine environment. However, to date, this research has been very disparate. Thus, it remains unclear what the timeframe for the biodegradation of such marine biodegradable plastics actually is. The aim of this work was to determine the rate of biodegradation of PHA in the marine environment and apply this to the lifetime estimation of PHA products. This provides the clarification required as to what 'marine biodegradation of PHA' means in practicality and allows the risks and benefits of using PHA to be transparently discussed. It was determined that the mean rate of biodegradation of PHA in the marine environment is 0.04–0.09 mg·day −1 ·cm −2 ( p = 0.05) and that, for example, a PHA water bottle could be expected to take between 1.5 and 3.5 years to completely biodegrade. Highlights: All relevant literature relating to the marine biodegradation of PHA is collated. The mean rate of biodegradation is 0.04–0.09 mg·day −1 ·cm −2 ( p = 0.05). Lifetimes of PHA products in the marine environment are estimated. A PHA bottle has a mean lifetime of 1.5–3.5 yrs, a thin film lasts 0.1–0.2 yrs.